Self-reported oral problems, compared with clinical assessment in an epidemiological study - S Airila-Ma°nsson (Journal compilation 2007 Blackwell Munksgaard, 2007)
To study self-reported oral problems in relation to periodontal clinical findings in an epidemiological investigation.